Juniarti, Sonia Analisis Kesulitan Siswa Dalam Menyelesaikan Soal Materi Operasi Bilangan Pecahan Kelas VII SMP - Sonia Juniarti; Yuli Fitrianti; Retni Paradesa (Faculty of Education and Teacher Training, State Islamic University of Sulthan Thaha Saifuddin Jambi, 2022)
This study aims to see and describe the difficulties of students in solving problems of fractional number operations in class VII and the factors that influence these difficulties. The type of research used is descriptive qualitative, qualitative research method developed by Moleong which consists of the preparation stage, implementation stage and completion stage. The subjects of this study were seventh grade students of SMP Karya Ibu Palembang. The data collection technique used is a test instrument that has been validated by three mathematicians and interviews using non-structural methods. The data analysis techniques used are 1) data reduction, 2) data presentation, and 3) conclusion drawing. The results of this study are: 1) This study has found out what difficulties are experienced by students in solving fractional number operation test questions 2) Factors that influence students so that they experience difficulties in solving fractional number operation test questions